OP49 Socioeconomic Status and Late Adolescent Trajectories of Smoking, Drinking, and Psychiatric Distress. (17th September 2012) - Green, MJ; Leyland, AH; Sweeting, H; Benzeval, M
Abstract : Background: Problems with smoking, alcohol use and psychiatric distress usually develop in adolescence and often co-occur. These problems may be inter-related but their co-occurrence could result from a common cause such as socioeconomic disadvantage. Methods: The Twenty–07 Study includes self-reported data on smoking, alcohol use and psychiatric symptoms (GHQ–12) from 1, 515 adolescents at approximate ages of 15 (baseline), 16 and 18. Latent class analysis (n=1238 with valid data) was used to identify distinct patterns of late adolescent development in smoking, alcohol use and psychiatric distress and relate these to various indicators of socioeconomic status (leaving school at 16, baseline area deprivation, and baseline parental measures of social class, education, housing tenure, income, employment status and family structure) whilst adjusting for gender. Results: Four latent classes were identified: 1) a low-risk class with low levels of smoking at all ages, low early drinking, moving towards regular drinking at age 18, and low levels of psychiatric symptoms; 2) a class with similar patterns for smoking and drinking but with high levels of psychiatric distress; 3) a class which engaged with alcohol earlier, many of whom were heavy drinkers by age 18, and had medium levels of distress; and 4) a high-risk class who engaged early with both smoking and drinking, most of whom were heavy smokers by age 18, and had medium and increasing levels of distress. In unadjusted analyses most indicators of socioeconomic disadvantage were associated with raised odds of membership in the high-risk class (reference group: low-risk class). With mutual adjustment for gender and all socioeconomic variables, those leaving school at 16 (OR 6.01; 95% CI 3.93–9.17) and in rented accommodation (OR 1.74; 1.19–2.56) still had significantly raised odds of membership in the high-risk class relative to those staying in school or in owner-occupied accommodation. Rented accommodation was protective for membership in the class with drinking but not smoking problems (OR 0.51; 0.30–0.86) and those in the most deprived areas were less likely to be in the class with psychiatric distress only (OR 0.37; 0.17–0.83) than those in more affluent areas. Conclusion: Socioeconomic disadvantage is implicated as a common cause of smoking, alcohol use, and psychiatric distress. Relationships with socioeconomic status are complex however and depend on the combination of outcomes, for example, trajectories with drinking but not smoking problems and those with psychiatric distress alone were more likely at the higher end of the socioeconomic distribution.